2001
DOI: 10.1080/02671520010011851
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion from school: a view from Scotland of policy and practice

Abstract: This paper reports research on the nature and extent of exclusion from school in Scotland 1994± 6. The research involved: documentary analysis of local authority policies on exclusion, supplemented by telephone interviews with of® cials responsible for the operation of policy; a survey of 176 headteachers; an analysis of information about 2,710 excluded pupils; and case studies of eight secondary and four primary schools. A wide variation in local authority policy was found although most authorities emphasized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…For the full research findings seeHodgson (2001). 3 This is consistent with the findings ofMunn et al (2001) who found that the peak age of both fixed-term and permanent exclusions is 14/15 years. It also corresponds to longitudinal research, which generally shows a peak age of first offence between the ages of 13 and 15 years(Farrington 1994).…”
supporting
confidence: 88%
See 1 more Smart Citation
“…For the full research findings seeHodgson (2001). 3 This is consistent with the findings ofMunn et al (2001) who found that the peak age of both fixed-term and permanent exclusions is 14/15 years. It also corresponds to longitudinal research, which generally shows a peak age of first offence between the ages of 13 and 15 years(Farrington 1994).…”
supporting
confidence: 88%
“…Likewise, the Audit Commission (1996, p.66) found that 42% of offenders of school age who were sentenced in the youth court had been excluded from school. Both works were to be readily cited by academics and politicians, and references to both studies were to appear in virtually every piece of literature considering youth crime and the inevitable policy deliberations flowing from this (see, for example, Gilbertson 1998;Social Exclusion Unit 1998;Smith 1998;Parsons 1999;NACRO 2000;Munn et al 2001;Ball and Connolly 2000;Pomeroy 2000). However, closer scrutiny of the findings of both Graham and Bowling and of the Audit Commission's research in relation to exclusion and crime suggests their robustness may be questionable (Hodgson 2001).…”
Section: School Exclusion and Crimementioning
confidence: 99%
“…Even if school policies suggest that exclusion should be used as a last resort, reserved for only the most serious and persistent offences ( Gregory & Weinstein, 2008a; Skiba & Peterson, 1999 ; Skiba, Trachok, Chung, Baker, & Hughes, 2012 ), research evidence suggests that minor offences can also provoke this type of punishment ( Munn, Cullen, Johnstone, & Lloyd, 2001 ; Skiba, 2014 ). Fenning et al, (2012) provide a case in point: their research concluded that suspension and expulsion were the most common types of punishment for minor problems such astardiness and school truancy.…”
Section: Introductionmentioning
confidence: 99%
“…There is, in any case, evidence that the characteristics of neither children nor schools fully account for rates of exclusion. Thus, it has been found that schools with very similar characteristics and intakes may differ significantly in the rate at which children are excluded because of their behaviour (Galloway, Martin, & Wilcox, 1985; Munn, Cullen, Johnstone, & Lloyd, 2001; Osler et al., 2001, Vulliamy & Webb, 2000). As suggested in the preceding review, an alternative possibility lies in the relationship between teachers’ beliefs and practices, the organizational ethos of schools, and rates of exclusion.…”
Section: Introductionmentioning
confidence: 99%